2020
DOI: 10.1111/1462-2920.15178
|View full text |Cite
|
Sign up to set email alerts
|

Extreme storms cause rapid but short‐lived shifts in nearshore subtropical bacterial communities

Abstract: Summary Climate change scenarios predict tropical cyclones will increase in both frequency and intensity, which will escalate the amount of terrestrial run‐off and mechanical disruption affecting coastal ecosystems. Bacteria are key contributors to ecosystem functioning, but relatively little is known about how they respond to extreme storm events, particularly in nearshore subtropical regions. In this study, we combine field observations and mesocosm experiments to assess bacterial community dynamics and chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 106 publications
0
18
1
Order By: Relevance
“…A higher frequency of extreme precipitation events (tropical cyclones) and more precipitation associated with non-cyclone storm events between extensive droughts is predicted in the regions surrounding the NRE, but also other globally distributed systems—making precipitation frequency a regional to global concern 109 – 112 . This is particularly true for estuaries and coastal systems where plankton community structure and biomass are altered by storms of varying severity 113 115 . Based the data presented here and prior results from other estuaries 13 , 16 , 17 , reductions in total PicoP biomass and promotion of larger PEUK are expected in temperate/tropical estuaries poised to receive more precipitation via moderate to extreme storms.…”
Section: Resultsmentioning
confidence: 99%
“…A higher frequency of extreme precipitation events (tropical cyclones) and more precipitation associated with non-cyclone storm events between extensive droughts is predicted in the regions surrounding the NRE, but also other globally distributed systems—making precipitation frequency a regional to global concern 109 – 112 . This is particularly true for estuaries and coastal systems where plankton community structure and biomass are altered by storms of varying severity 113 115 . Based the data presented here and prior results from other estuaries 13 , 16 , 17 , reductions in total PicoP biomass and promotion of larger PEUK are expected in temperate/tropical estuaries poised to receive more precipitation via moderate to extreme storms.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the adoption of novel molecular biomonitoring approaches (e.g., environmental DNA; Thomsen and Willerslev 2015 ) and high-throughput in situ imaging (e.g., camera traps; for a review, see Farley et al 2018 ) have more accurately recorded population and community shifts in response to major disturbance. These approaches have been successfully applied to collect data and assess the responses to extreme events across freshwater (e.g., Curtis et al 2020 , Mächler et al 2021 ) and marine (Anglès et al 2015 , Grossmann et al 2015 , Ares et al 2020 , DiBattista et al 2020 ) species that are challenging to identify or collect using conventional species-capture approaches. The empirical tools listed above, particularly when used in combination with conventional sampling approaches, can provide robust biological, chemical, and physical data to maximize the power and timeliness of ecosystem studies.…”
Section: Recommended Approaches To Enhance Studies Of Extreme Eventsmentioning
confidence: 99%
“…For example, storm impacts could be controlled by proximity to urban or agricultural environments with potential for runoff, local topography and hydrology of the coastal region, and characteristics of the storm (e.g., intensity, duration, and path). Previous studies from different locations have shown variable degrees of impact from extreme storms toward microbial communities (Okinawa, Japan: Ares et al, 2020 ; Pamlico Sound, North Carolina: Paerl et al, 2001 ; Peierls et al, 2003 ; Oahu, Hawaii: De Carlo et al, 2007 ; Yeo et al, 2013 ; New Orleans, Louisiana: Sinigalliano et al, 2007 ; and Houston, Texas: Steichen et al, 2020 ). Increased understanding of geographic region-specific shifts in microbial community composition and functional potential following extreme storms is vital to interpreting disruptions to nutrient cycling processes and the overall health of a coastal ecosystem.…”
Section: Introductionmentioning
confidence: 99%